Synthesis and Characterization of Thermally-Stable and Soluble Perylene Bisimide - Zhang, Lin; Xu, Yewei; Zhu, Fanghua; Sun, Jingyuan (Asian Journal of Chemistry, 2010)
N,N'-Didodecyl-1,7-di(4-tert-butylphenoxy)perylene-3,4,9,10-tetracarboxylic acid bisimide (4a) and N,N'-didodecyl-1,6,7,12-tetra(4-tert-butylphenoxy)perylene-3,4,9,10-tetracarboxylic acid bisimide (4b) have been synthesized derived from 1,7-dibromo- and 1,6,7,12-tetrabromo-perylene tetracarboxylic acid bisanhydride. Because these perylene bisimides exhibit good solubility, the structures of 4a and 4b are characterized by FT-IR, 1H and 13C NMR and mass spectroscopy. The results show an agreement with the proposed structures. The optical properties of perylene bisimides have been determined by UV/vis and fluorescence spectroscopy. It has been shown that the displacement of bromines by 4-tert-butylphenoxy groups causes the significant red shift and the increase in the number of 4-tert-butylphenoxy groups determines the red shift location. Due to electron inductive effect which was caused by 4-tert-butylphenoxy groups, the LUMO of 4a and 4b are 3.89 and 3.86 eV, respectively. TG measurements show that 4a and 4b possess good thermal stability with high decomposition temperatures (> 400 ºC).